Depression levels and symptoms in athletes with chronic gastrocnemius myofascial pain: A case-control study - San-Antolina, M.; Rodriguez-Sanz, D.; López-López, D.; Romero-Morales, C.; Carbajales-Lopez, J.; Becerro-de-Bengoa-Vallejo, R.; Losa-Iglesias, M. E.; Calvo-Lobo, C. (Physical Therapy in Sport, 2020)
Objective: To determine the influence of depression symptoms and levels in athletes with gastrocnemius myofascial pain with respect to healthy athletes. In addition, to determine a prediction model for kinesiophobia symptoms based on descriptive data and gastrocnemius myofascial pain presence. Design: Secondary case-control. Setting: Outpatient clinic. Participants: A sample of 50 athletes was recruited and divided into athletes with chronic gastrocnemius myofascial pain (n = 25) and healthy athletes (n = 25). Main outcome measurements: Depression symptoms scores and levels were self-reported by athletes using the Beck Depression Inventory - II (BDI-II). Results: Statistically significant differences for depression symptoms scores (P = 0.011) with a moderate effect size (d = 0.77) and depression levels (P = 0.036) were found between both groups showing greater depression symptoms and levels in athletes with gastrocnemius myofascial pain (13.00 ± 13.50 points; range from 0 to 28 points) versus healthy athletes (4.00 ± 7.00 points; range from 0 to 19 points). Higher depression symptoms scores of BDI-II were only predicted by the presence of gastrocnemius myofascial pain in athletes (R2 = 0.134; ß = +5.360; F[1,48] = 7.428; P = 0.009). Conclusions: Greater depression symptoms and levels were exhibited for athletes with gastrocnemius myofascial pain compared to healthy athletes. In addition, depression score of athletes was only predicted by the presence of gastrocnemius myofascial pain.